Interaction and dynamic changes of microbial communities and volatile flavor compounds during the fermentation process of coffee flower rice wine - Liu, Kunyi; Su, Rui; Wang, Qi; Shen, Xiaojing; Jiang, Bin; Yang, Liran; Li, Zelin; Zheng, Jia; Li, Pingping (Frontiers in Microbiology, 2024)
To develop a unique flavor of rice wine, coffee flowers (by-products of the coffee industry) were added because of their biologically active compounds that are conducive to health, and the fermentation parameters were optimized. In addition, the dynamic changes of microbial communities and volatile flavor compounds (VFCs) during the different fermentation stages were investigated. After the optimization of the fermentation parameters, a novel product, i.e., the coffee flower rice wine (CFRW), was obtained with a bright yellow transparent, fragrant, and harmonious aroma and mellow and refreshing taste by sensory evaluation, when 4.62% of the coffee flowers and 1.93% koji were added and fermented at 24.10°C for 3.88 days. The results showed that Lactococcus was the dominant bacteria, accounting for 87.0–95.7%, while Rhizopus and Cladosporium were the main fungi, accounting for 68.2% and 11.3% on average, respectively, in the fermentation process of the CFRW. Meanwhile, twenty-three VFCs were detected in the CFRW, which included three alcohols, six terpenes, ten esters, three aromatics, and one furan. The correlation analysis revealed that there were 16 significant positive correlations and 23 significant negative correlations between the bacterium and VFCs (|ρ| > 0.6, p < 0.05), while there were 12 significant positive correlations and one significant negative correlation between the fungi and VFCs (|ρ| > 0.6, p < 0.05). Furthermore, five VFCs, including linalool, geraniol, ethyl acetate, 1-hexanol, and 3-methyl-1-butanol, contributed vital flavors to the CFRW, and they were all significantly negatively correlated with the changes of Massilia and Acinetobacter (|ρ| > 0.6, p < 0.05). Moreover a significant positive correlation was found between the relative abundance of Lactococcus and the contents of 3-methyl-1-butanol and ethyl acetate (|ρ| > 0.6, p < 0.05). Therefore, this study provides a valuable theoretical basis for further improving the quality and production technology of CFRW.